THE EFFECT OF INFLATION AND IDR EXCHANGE RATE ON NET ASSETS VALUE OF STOCK MUTUAL FUNDS IN INDONESIA WITH THE ROLE OF IDX COMPOSITE AS MEDIATING VARIABLE - Luqman Hakim; Muhamad Ikra; Nuraeni Nuraeni (ABNUS Publisher, 2022)
Net Asset Value (NAV) is the rational market value of a mutual fund's securities and other assets with fewer liabilities. Net Asset Value can be used as a benchmark in monitoring the results of a mutual fund. Mutual fund results and performance cannot be separated from various internal and external factors. This study purposes to analyze the character of IHSG/ IDX Composite in mediating the effect of inflation and the rupiah exchange rate on the equity mutual funds’ NAV in Indonesia during the period of 2015-2019. This study benefits panel data with path analysis techniques by using the Smart PLS. The results show that inflation influences negatively and insignificantly on Equity Mutual Funds’ NAV. IDX Composite has negative and insignificant effect on Equity Mutual Funds’ NAV, and the Rupiah Exchange Rate have the positive and significant influence on Equity Mutual Funds’ NAV. The value of the coefficient of determination is 49.8%, which means how much the Equity Funds’ NAV can be explained by Inflation, IDX Composite, and Rupiah Exchange Rate. Moreover, the remaining 50.2% is effected by other variables.